1984
DOI: 10.1152/ajpheart.1984.247.6.h895
|View full text |Cite
|
Sign up to set email alerts
|

Skin blood flow reduction induced by cigarette smoking: role of vasopressin

Abstract: The effect of vasopressin released by cigarette smoking on blood pressure (BP), heart rate (HR), and skin blood flow (SBF) was investigated in 12 normotensive habitual smokers. At a 1-wk interval, each subject smoked within 10 min two cigarettes before and after intravenous injection of either the specific vascular vasopressin antagonist d(CH2)5Tyr(Me)AVP (5 micrograms/kg) or its vehicle administered in double-blind fashion. SBF was assessed with a laser Doppler flowmeter. Smoking increased plasma vasopressin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…As for the acute e¤ect of smoking on peripheral circulation, vasoconstriction by nicotine and decrease of blood ßow in skin by increase of vasopressin secretion was reported (Waeber et al 1984). Three of seven RAs did not show statistically signiÞcantly decrease 1 min after commencement.…”
Section: Discussionmentioning
confidence: 95%
“…As for the acute e¤ect of smoking on peripheral circulation, vasoconstriction by nicotine and decrease of blood ßow in skin by increase of vasopressin secretion was reported (Waeber et al 1984). Three of seven RAs did not show statistically signiÞcantly decrease 1 min after commencement.…”
Section: Discussionmentioning
confidence: 95%
“…Smoking induces ␣1-adreno-mediated vasoconstriction and release vasopressin [15,28,29], which have been shown to reduce non-nutritive blood flow and increase oxygen uptake [24]. In addition, smoking-induced increase of skin sympathetic activity and arterial baroreflex alterations, which also affect the non-nutritive blood flow, may play a role as well [15, 24, 29 -31].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine can inhibit nitric oxide release and decrease endothelium-dependent vasorelaxation (Mayhan and Patel, 1997;Mayhan and Sharpe, 1999;Black et al, 2001;Conklin et al, 2001). In addition, both direct vasoconstriction and relaxation induced by nicotine have been reported previously (Waeber et al, 1984;Toda et al, 1995;Zhang et al, 1998;Wang and Wang, 2000). Although clinical and in vivo studies have demonstrated that nicotine decreases uterine blood flow in pregnancy, the direct effect of nicotine on uterine artery contractility has not been studied.…”
Section: Effect Inhibition Of Enos With Nmentioning
confidence: 97%